Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Dual-ion synergistic biopolymer hydrogel: Efficient acid blue 113 adsorption with algal safety - Yanping Jia; Shuo Li; Yaoxin Hu; Jian Zhang; Fei Du; Ruixuan Cai; Lanhe Zhang (Journal of Water Process Engineering, 2026)

Electric field-assisted simultaneous microextraction of ultrashort- to long-chain perfluorocarboxylic acids prior to HPLC-MS/MS quantification - Fenghong Wei; Pei Wang; Junjun Hu; Yanping Zheng; Xiaojia Huang (Journal of Hazardous Materials, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

The PorV protein as a cross-protective antigen against Riemerella anatipestifer infection - Sen Li; Yanhua Wang; Xiong Liu; Keke Ren; Yanping Deng; Yuncai Xiao; Sishun Hu; Zili Li; Hongbo Zhou; Zhengfei Liu; Zutao Zhou (Veterinary Microbiology, 2026)

Integrative histological and multi-omics analyses reveal hormone-driven cell regeneration mechanisms during postharvest wound healing in melon - Congcong Wang; Yanping Hu; Baibi Zhu; Jihao Chen; Feng Wang; Shiqi Lu; Min Wang (Postharvest Biology and Technology, 2026)

Explainable daily warning of algal concentration exceedance from SHAP-guided temperature and light thresholds - Dawei Xu; Yanping Hu; Shouye Yang; Lu Wang; Long Wang (Journal of Environmental Chemical Engineering, 2026)

A Study on the Species Diversity, Mating Types, and Clinical Relevance of Trichophyton mentagrophytes/interdigitale Complex Infections in Guizhou Province - Wei Hu; Kexin Xu; Jing Zhou; Wanglan Luo; Songgan Jia; Xiangyu Liu; Zhengling Shang; Yinhui Jiang; Zhi Liu; Yanping Jiang (Mycopathologia, 2026)

Recyclable standardized sludge for performance evaluation of low-temperature drying units: Preparation and feasibility verification - Yuting Qin; Yanping Guo; Yongyou Hu; Jingyu Liu; Guanying Huang; Guanghuan Li; Haochun Chen; Qingying Huang (Journal of Environmental Management, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Overall quality maintenance and metabolite changes of fresh Cistanche deserticola Y.C.Ma stems treated by 1-methylcyclopropene during cold storage - Longxia Wen; Shuangxi Qian; Yanping Wang; Mingxing Xu; Yazhou Shao; Xu Zhang; Lijun Zhang; Yongchen Hua; Guolin Chai; Fangdi Hu (Postharvest Biology and Technology, 2026)

Estrus synchronization and follicular development patterns in jennies - Naerhulan Ayiken; Yeertai Tuohudashen; Younusi Huojiaabudula; Abudula Abudureyimu; Hongli Wang; Mingyang Geng; Guangdong Hu; Yanping Wang; Weibin Zeng (Journal of Equine Veterinary Science, 2026)

Intraspecific Variations and Characteristics of Clinical, Physiological, and Antifungal Susceptibility Profiles of Trichophyton rubrum in Southwest China - Yanni Deng; Wanglan Luo; Hao Hu; Jing Zhou; Qian Zhang; Songgan Jia; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Phloretin enhances the efficiency of sheep oocyte IVM and early embryonic development by bolstering antioxidant defenses, inhibiting apoptosis, and promoting development - Xu Li; Shuhong Tang; Yinwei Zheng; Ruiguo Zhao; Feifan Xu; Naerhulan Ayiken; Guangdong Hu; Yanping Wang; Weibin Zeng (Reproductive Biology, 2026)

Preparation of sawdust-based degradable mulch film and nutrient slow-release performance evaluation - Xianghai Kong; Rongxi Hu; Zerong Song; Xinxin Zhai; Ziyu You; Yuhao Wang; Pan Zhao; Xiaofeng Lu; Rongjun Zhang; Yanping Zhu; Dongfang Wang; Dongqing Cai (Journal of Environmental Chemical Engineering, 2026)

Molecular Epidemiology, Mating Types, Clinical, and Physiological traits of Microsporum canis in Humans and Companion Animals (Cats and Dogs) in the Guiyang Region, Southwest China - Hao Hu; Bin Jiao; Yanni Deng; Wanglan Luo; Jing Zhou; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhengrong Wang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Transcriptome analysis of possible genetic-level defects in the use of large-sized Chinese mitten crab ( Eriocheir sinensis ) parents for breeding - Fujun Xuan; Jinghao Hu; Lei Gao; Ruifang Wang; Yanping Yang; Ying Pan; Jun Zhou; Rongchen Liu (Invertebrate Reproduction & Development, 2026)

Exfoliation characteristics of tetrahydrofuran on surface-active structure of different coals and its inhibition effect on oxidation - Jun Guo; Yunfei Wu; Hu Wen; Yin Liu; Yongfei Jin; Changming Chen; Yanping Quan (Fuel, 2026)

A new method of consistency evaluation of brain drugs: a case study of edaravone - Liqiang Gu; Yanping Hu; Yinfang Lai; Sheng Zhang; Haoran Wang; Xiaozhen Xu; Lingfang Chen; Yuhua Shi; Jiechao Chen; Xiaochun Sun; Yuan Zhang; Lingzhi Hu (Regulatory Toxicology and Pharmacology, 2025)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Study on the mechanism of influence of group extraction on low-temperature spontaneous combustion characteristics of lignite - Changming Chen; Jun Guo; Hu Wen; Yin Liu; Bo Gao; Yunfei Wu; Yanping Quan (Fuel, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Interfacially synergistic Photothermal enhancement for solar evaporation by palygorskite-carbon nanotube/chitosan aerogels - Yimin Qu; Changliang Lu; Gaofeng Zhang; Zhu Hu; Dajian Huang; Xiaohu Qiang; Yanping Wang (Desalination, 2025)

Overexpression of CYP6CY36 and CYP380C34 contributes to metabolic resistance of Myzus persicae (Sulzer) to flupyradifurone - Qiuling Tang; Jinfeng Hu; Chengfeng Zheng; Wei Zhang; Jie Bi; Yanping He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Naringenin attenuates Mandarin fish ranavirus (MRV)-induced hyperinflammation through the inhibition of MAPK and NF-κB signaling pathways - Ziye Zhang; Yanping Ma; Xinru Gao; Chaojiao Hu; Le Hao; Huijie Lu; Yugu Li; Zhenxing Liu (Fish & Shellfish Immunology, 2025)

High-resolution profiling observation of carbon source dynamics in a mussel farm in the Changjiang River estuary during early autumn - Dawei Xu; Di Wu; Shouye Yang; Yanping Hu; Kui Wang (Journal of Oceanology and Limnology, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

An advanced numerical model for dynamic daylight and energy consumption analysis of thermal-responsive complex fenestration system with adaptive solar absorption - Yang Ming; Mingke Hu; Xiao Liu; Yanping Yuan; Yupeng Wu (Energy and Buildings, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Study of the interaction between polysaccharides and liposomes based on low-field nuclear magnetic resonance - Tingting Zhang; Heng Yu; Chenping Li; Yanping Wang; Chenxi Zheng; Yingli Hu; Jianzhong Han; Jianhua Liu; Weilin Liu (Food Bioscience, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Monosome Stalls the Translation Process Mediated by IGF2BP in Arcuate Nucleus for Puberty Onset Delay - Yifen Shen; Le Zhang; Tao Yang; Xiaosong Li; Chao Liu; Hongmei Li; Yanping Hu; Hao Shen; Hua Li; Yuriy L. Orlov; Shasha Zhou; Yihang Shen (Molecular Neurobiology, 2025)

A scale for evaluating the willingness of national forest farm to participate in forest carbon sink project - Guanqing Wu; Degang Fu; Yingchao Xing; Huizhen Duan; Yifan Wang; Jihuai Hu; Yanping Wang; Fengjuan Zhang (Journal of Environmental Management, 2025)

Forest transformation increases soil N2O fluxes in an unmanaged Moso bamboo forest - Yibo Yan; Xueying Tu; Hui Zhang; Yang Lv; Yihui Zhao; Ao Hu; Yanping Wu; Caixian Tang; Yixiang Wang (Forest Ecology and Management, 2025)

Phosphorus-oxygen modified anthracene-based emitters for high-efficiency deep-blue OLEDs approaching the BT.2020 blue standard - Ruicheng Wang; Yihong Zhu; Dehua Hu; Jie Hu; Si-wei Chen; Jieying Lin; Longjiang Xing; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2025)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Ecologically friendly remediation of groundwater sulfamethoxazole contamination: Biologically synergistic degradation by thermally modified activated carbon-activated peracetic acid in porous media - Si Li; Ruizhe Xu; Luochao Wan; Chaomeng Dai; Jixiang Li; Xueji You; Yanping Duan; Xiaoying Lai; Zhi Li; Jifeng Guo; Yalei Zhang; Jiajun Hu; et al. (Journal of Hazardous Materials, 2024)

Effects of hypobaric hypoxia on human physiological and psychological responses in hot-humid environments - Yue Hu; Liangliang Sun; Guorong Xu; Xiaowen Su; Yanping Yuan (Building and Environment, 2024)

Sustainable upcycling of copper from waste printed circuit boards with the assistance of tannic acid and Fe3+ to a magnetic heterogeneous catalyst - Yanping Zhong; Sisi Hu; Jinghua Xu; Zhenguo Chen; Shuhua Wang (Journal of Environmental Management, 2024)

Virtual screening reveals fluorescent probes for detecting Pan-Zinc center activity in serum MMPs: A potential biomarker for early tumor screening - Shang Ju; Yi Xiang; Yajun Xie; Lei Zuo; Juqiong Li; Xiaorong Li; Yanping Wang; Qin Huang; Min Zhang; Xiaomian Wu; Yuanyuan Wang; Qiong Shi; et al. (Chemical Engineering Journal, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

Antidepressant effects of activation of infralimbic cortex via upregulation of BDNF and β-catenin in an estradiol withdrawal model - Jiali Chen; Yiying Zhou; Miaojun Lai; Yanping Zhang; Yifang Hu; Dingding Zhuang; Wenhua Zhou; Yisheng Zhang (Psychopharmacology, 2024)
Rationale Clinical and preclinical studies have demonstrated that estradiol withdrawal after delivery is one of important factors involved in the pathogenesis of postpartum depression (PPD). The infralimbic cortex (IL) is related to anxiety and mood disorders. Whether IL neurons mediate PPD is still unclear. Objectives This study was to observe the antidepressant effect and expression of BDNF and β-catenin in IL by allopregnanolone (ALLO) treatment or the selective activation or inhibition of IL neurons using a chemogenetic approach in a pseudopregnancy model of PPD. Methods Administration of estradiol combined with progesterone and the abrupt withdrawal of estradiol simulated the pregnancy and early postpartum periods to induce depression in ovariectomized rats. The relative expression levels of β-catenin and BDNF were observed by western blotting. Results Immobility time was significantly increased in the forced swim test and open-arm movement was reduced in the elevated plus maze test in the estradiol-withdrawn rats. After ALLO treatment, the immobility time were lower and open-arm traveling times higher than those of the estradiol-withdrawn rats. Meanwhile, the expression level of BDNF or β-catenin in the IL was reduced significantly in estradiol-withdrawn rats, which was prevented by treatment with ALLO. The hM3Dq chemogenetic activation of pyramidal neurons in the IL reversed the immobility and open-arm travel time trends in the estradiol-withdrawal rat model, but chemogenetic inhibition of IL neurons failed to affect this. Upregulated BDNF and β-catenin expression and increased c-Fos in the basolateral amygdala were found following IL neuron excitation in model rats. Conclusions Our results demonstrated that pseudopregnancy and estradiol withdrawal produced depressive-like behavior and anxiety. ALLO treatment or specific excitement of IL pyramidal neurons relieved abnormal behaviors and upregulated BDNF and β-catenin expression in the IL in the PPD model, suggesting that hypofunction of IL neurons may be involved in the pathogenesis of PPD.

The applicability of a SIF-based mechanistic model for estimating GPP at the canopy scale - Yanping Liu; Zhaoyong Hu; Genxu Wang; Arthur Gessler; Shouqin Sun (Agricultural and Forest Meteorology, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Evolution of runoff discharge patterns and risk assessment of water inrush in mountainous railroad tunnels - Xu Yang; Dandan You; Xin Gao; Qi Li; Xinhao Hu; Saixing Zeng; Jingxiao Zhang; Yanping Hu; Lanxin Kang (Natural Hazards, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

The impact of microbial inoculants on large-scale composting of straw and manure under natural low-temperature conditions - Yanping Wang; Qi Yu; Chuang Zheng; Yanbo Wang; Heshu Chen; Shijia Dong; Xiaomei Hu (Bioresource Technology, 2024)

Determining the response of ecological drought to meteorological and groundwater droughts in Northwest China using a spatio-temporal matching method - Tianliang Jiang; Xiaoling Su; Yanping Qu; Vijay P. Singh; Te Zhang; Jiangdong Chu; Xuexue Hu (Journal of Hydrology, 2024)

Correction: Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2024)

Intervention effects of fructooligosaccharide and astragalus polysaccharide, as typical antibiotic alternatives, on antibiotic resistance genes in feces of layer breeding: advantages and defects - Yanping Hu; Jingjing Wei; Yongze Yuan; Hongkui Wei; Yuanfei Zhou; Naidong Xiao; Juan Xiong; Zhuqing Ren; Jian Peng; Changzheng Cui; Zhongxin Zhou (Journal of Hazardous Materials, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Consequences of excess urea application on photosynthetic characteristics and nitrogen metabolism of Robinia pseudoacacia seedlings - Yong Zhang; Rui Liu; Zhenshan Liu; Yanping Hu; Zhuyuan Xia; Bin Hu; Heinz Rennenberg (Chemosphere, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2023)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Multi-omics analysis of oxidative stress and apoptosis in hepatopancreas cells induced by Polyascus gregaria parasitizing the Eriocheir sinensis - Shiwei Zhao; Qingbiao Hu; Hongbo Jiang; Yingying Zhao; Yanping Wang; Chengcheng Feng; Xiaodong Li (Fish & Shellfish Immunology, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Study on thermal properties of bio-char prepared by photo-thermal pyrolysis - Dexin Huang; Yankui Wang; Gongxiang Song; Song Hu; Hanjian Li; Yanping Zhang; Yi Wang; Sheng Su; Saad A. El-Sayed; Jun Xiang (Biomass and Bioenergy, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Effectively synthesized functional Si-doped carbon dots with the applications in tyrosinase detection and lysosomal imaging - Chenfang Miao; Xin Zhou; Xiaoyang Huang; Jiyue Huang; Yanping Chen; Yuebin Liu; Xiaomu Hu; Lingjun Zeng; Shaohuang Weng; Huixing Chen (Analytica Chimica Acta, 2023)

Risk factors of vestibular migraine-related brain white matter lesions - Yu Shen; Defu Li; Qian Cao; Mengyao Hu; Zhou Hou; Lijun Xu; Yanping Li; Daojun Hong (Acta Neurologica Belgica, 2023)

The rhizosphere soil properties and bacteria community of poplar are affected by magnetic field under salt condition - Han Wenhao; Wang Nianzhao; Hu Jihuai; Yan Kun; Ma Fengyun; Tian Huimei; Wang Yanping (Rhizosphere, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

First kinetics verification of the useful H2Ogas inhibition on the thermal regeneration of spent activated carbon in flue gas desulfurization - Hanyu Deng; Wenzhen Cai; Lanhe Zhang; Yanping Jia; Xiaoqiang Wang; Qing Zong; Guishi Cheng; Xiaoying Hu; Changqing Dong; Ying Zhao (Fuel, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

A mathematical model for phosphorus interactions and transport at the sediment-water interface in a large shallow lake - Yanping Wang; Zhaoliang Peng; Gang Liu; Hui Zhang; Xiangqian Zhou; Weiping Hu (Ecological Modelling, 2023)

Auxin and CmAP1 regulate the reproductive development of axillary buds in Chinese chestnut (Castanea mollissima) - Yunhe Cheng; Lili Cheng; Guanglong Hu; Xiaomeng Guo; Yanping Lan (Plant Cell Reports, 2022)

Genomic distribution of signal transducer and activator of transcription (STAT) family in colorectal cancer - Yanping Hu; Yifen Shen; Yang Zhao; Ying Tang; Chao Liu; Yongchun Gu; Tao Yang; Yihang Shen (Human Cell, 2022)

Early-Holocene Paleo-Tropical Cyclone Activity Inferred from a Sedimentary Sequence in South Yellow Sea, East Asia - Geng Liu; Xibin Han; Yanping Chen; Jun Li; Lehui Song; Xin Zhou; Bangqi Hu; Liang Yi (Journal of Earth Science, 2022)

Analysis and Health Risk Assessment of Potentially Toxic Elements in Three Codonopsis Radix Varieties in China - Ruibin Bai; Yanping Wang; Yajie Zhang; Yan Wang; Jiabing Han; Zixia Wang; Jing Zhou; Fangdi Hu (Biological Trace Element Research, 2022)

An Improved Dueling Deep Double-Q Network Based on Prioritized Experience Replay for Path Planning of Unmanned Surface Vehicles - Zhengwei Zhu; Can Hu; Chenyang Zhu; Yanping Zhu; Yu Sheng (Journal of Marine Science and Engineering, 2021)
Unmanned Surface Vehicle (USV) has a broad application prospect and autonomous path planning as its crucial technology has developed into a hot research direction in the field of USV research. This paper proposes an Improved Dueling Deep Double-Q Network Based on Prioritized Experience Replay (IPD3QN) to address the slow and unstable convergence of traditional Deep Q Network (DQN) algorithms in autonomous path planning of USV. Firstly, we use the deep double Q-Network to decouple the selection and calculation of the target Q value action to eliminate overestimation. The prioritized experience replay method is adopted to extract experience samples from the experience replay unit, increase the utilization rate of actual samples, and accelerate the training speed of the neural network. Then, the neural network is optimized by introducing a dueling network structure. Finally, the soft update method is used to improve the stability of the algorithm, and the dynamic ϵ-greedy method is used to find the optimal strategy. The experiments are first conducted in the Open AI Gym test platform to pre-validate the algorithm for two classical control problems: the Cart pole and Mountain Car problems. The impact of algorithm hyperparameters on the model performance is analyzed in detail. The algorithm is then validated in the Maze environment. The comparative analysis of simulation experiments shows that IPD3QN has a significant improvement in learning performance regarding convergence speed and convergence stability compared with DQN, D3QN, PD2QN, PDQN, PD3QN. Also, USV can plan the optimal path according to the actual navigation environment with the IPD3QN algorithm.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Retention of nitrogen and phosphorus in Lake Chaohu, China: implications for eutrophication management - Yanping Wang; Xiangzhen Kong; Zhaoliang Peng; Hui Zhang; Gang Liu; Weiping Hu; Xiangqian Zhou (Environmental Science and Pollution Research, 2020)

Differential effects of three amendments on the immobilisation of cadmium and lead for Triticum aestivum grown on polluted soil - Shengze Zhang; Lingtong Quan; Yanping Zhu; Jin Yan; Xiaoman He; Jia Zhang; Xiaoming Xu; Zhubing Hu; Feng Hu; Yahua Chen; Zhenguo Shen; Yan Xia (Environmental Science and Pollution Research, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Acetylation of BmAtg8 inhibits starvation-induced autophagy initiation - Shengjie Xue; Fuxiang Mao; Dongbing Hu; Huihui Yan; Jihai Lei; Enoch Obeng; Yuefan Zhou; Yanping Quan; Wei Yu (Molecular and Cellular Biochemistry, 2019)

The distribution of plants and seed dispersers in response to habitat fragmentation in an artificial island archipelago - Jiajia Liu; Ferry Slik; David A. Coomes; Richard T. Corlett; Yanping Wang; Maxwell Wilson; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2019)
Aim Small, old‐growth forest fragments generally have more small‐seeded plants than large patches, due to the disappearance of large seed dispersing vertebrates. This pattern may differ for secondary forest fragments where differential migration ability rather than persistence of seed dispersers may be driving plant community assembly. In this study, we investigated the effect of habitat fragmentation on seed dispersers and plant community structure in regenerating forests. Location The Thousand Island Lake, China. Taxon Plants, birds and mammals. Methods We compiled diversity and abundance data for birds and mammals on islands in the Thousand Island Lake, China. We also surveyed the secondary plant communities and measured seed dispersal traits. Results Community‐weighted mean seed size of woody plants decreased with island size. This pattern was related to compositional difference of the dispersers. We found that mammal diversity and abundance was only weakly or not related to island size; whereas bird diversity and abundance increased strongly with island size. Density of bird‐dispersed plants was significantly positively related with island size. Since birds tend to disperse smaller seeds than mammals, the trend in seed size may have been a consequence of the shift in relative abundance of the two disperser guilds. Main Conclusions Differential responses of seed dispersers to habitat fragmentation may lead to pervasive shifts in the plant community structure of regenerating forest fragments. Our study highlights the importance of keeping large continuous forests in order to retain mammals and their dispersal capabilities.

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

The complete chloroplast genome sequence of Actinidia kolomikta from north China - Yanping Lan; Lili Cheng; Wugang Huang; Qingchang Cao; Zhijun Zhou; Anjin Luo; Guanglong Hu (Conservation Genetics Resources, 2018)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Improved isolation of cadmium from paddy soil by novel technology based on pore water drainage with graphite-contained electro-kinetic geosynthetics - Xianqiang Tang; Qingyun Li; Zhenhua Wang; Yanping Hu; Yuan Hu; Miklas Scholz (Environmental Science and Pollution Research, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Partial shade optimizes photosynthesis and growth in bayberry (Myrica rubra) trees - Guanghui Zeng; Yanping Guo; Jianxu Xu; Meijun Hu; Jie Zheng; Zhenwang Wu (Horticulture, Environment, and Biotechnology, 2017)

The complete chloroplast genome sequence of the endangered Chinese endemic tree Corylus fargesii - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Xueqiang Wang; Wugang Huang (Conservation Genetics Resources, 2017)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

The complete chloroplast genome sequence of Corylus chinensis Franch - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Wugang Huang (Conservation Genetics Resources, 2017)

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

Evidence of the Matthew effect in scientific research on mammals in the Chinese First-class National Protected Animals list - He Zhang; Yanping Hu; Yanming Zhang; Wenjing Li (Biodiversity and Conservation, 2015)

Orexin A attenuates the sleep-promoting effect of adenosine in the lateral hypothalamus of rats - Yanping Cun; Lin Tang; Jie Yan; Chao He; Yang Li; Zhian Hu; Jianxia Xia (Neuroscience Bulletin, 2014)

Effects of Cognitive Behavioral Therapy on Insomnia of Maintenance Hemodialysis Patients - Yongmei Hou; Peicheng Hu; Yanping Liang; Zhanyu Mo (Cell Biochemistry and Biophysics, 2014)

Impact of biochar application on nitrogen nutrition of rice, greenhouse-gas emissions and soil organic carbon dynamics in two paddy soils of China - Zubin Xie; Yanping Xu; Gang Liu; Qi Liu; Jianguo Zhu; Cong Tu; James E. Amonette; Georg Cadisch; Jean W. H. Yong; Shuijin Hu (Plant and Soil, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Soil Respiration and N2O Flux Response to UV-B Radiation and Straw Incorporation in a Soybean–Winter Wheat Rotation System - Zhenghua Hu; Hailing Cui; Shutao Chen; Shuanghe Shen; Hanmao Li; Yanping Yang; Cenzi Li (Water, Air, & Soil Pollution, 2013)

Preliminary assessment of heavy metal contamination in surface water and sediments from Honghu Lake, East Central China - Ying Hu; Shihua Qi; Chenxi Wu; Yanping Ke; Jing Chen; Wei Chen; Xiangyi Gong (Frontiers of Earth Science, 2012)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Utilization of microbial iron assimilation processes for the development of new antibiotics and inspiration for the design of new anticancer agents - Marvin J. Miller; Helen Zhu; Yanping Xu; Chunrui Wu; Andrew J. Walz; Anne Vergne; John M. Roosenberg; Garrett Moraski; Albert A. Minnick; Julia McKee-Dolence; Jingdan Hu; Kelley Fennell; et al. (BioMetals, 2009)